Emergency care capacity in Sierra Leone: A multicentre analysis - Zosia Bredow; Zoe Corbett; Moses Mohamed Tarawally; Lucy Jackson; Foday Tejan Mansaray; Santigie Sesay; Andrew Leather (African Journal of Emergency Medicine, 2024)
Background: The Disease Control Priorities Project estimates that over 50 % of annual mortality in low- and middle-income countries can be addressed by improved emergency care. Sierra Leone's Ministry of Health and Sanitation has highlighted emergency care as a national priority. We conducted the first multicentre analysis of emergency care capacity in Sierra Leone, using the Hospital Emergency Unit Assessment Tool (HEAT) to analyse 14 government hospitals across the country. Methods: HEAT is a standardised assessment that is recommended in the World Health Organisation Emergency Care Toolkit. It has been used comparably elsewhere. To analyse Sierra Leone's emergency care capacity with the HEAT data, we created the HEAT-adjusted Emergency Care Capacity Score. Purposeful sampling was used to select 14 government facilities nationwide. A multidisciplinary team was interviewed over a 2-day in-person visit to each facility. Results: Human Resources was the strongest parameter, scoring 49 %. All hospitals provided emergency cover 24/7. Emergency Diagnostic Services was the most severely limited parameter, scoring 29 %. 3 hospitals had no access to basic radiography. Infrastructure scored 47 %. 2 hospitals had adequate electricity supply; 5 had adequate clean, running water. No hospitals had adequate oxygen supply. Clinical services scored 39 %. 10 hospitals had no designated Emergency Unit, only 2 triaged to stratify severity. Signal functions scored 38 %. No hospitals had reliable access to emergency drugs such as adrenaline. The total HEAT-adjusted Emergency Care Capacity Score across all hospitals was 40 %. Conclusions: These data identify gaps that have already led to local interventions, including focussing emergency resources to a resuscitation area, and training multidisciplinary teams in emergency care skills. This facility-level analysis could feed into wider assessment of Sierra Leone's emergency care systems at every level, which may help prioritise government strategy to target sustainable strengthening of national emergency care.